1999
DOI: 10.1159/000008615
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Kinetics of Cooling of Kidneys: A Pig Model

Abstract: We determined the kinetics of cooling in multiple organ procurement for the kidney in a pig model. A biometric analysis by regression enables us to define the factors which influence the rate of temperature decrease: weight of the donor, average rate of perfusion and difference of temperature between the rectal temperature and the temperature of the perfusion solution at initiation of cooling. The description of the temperature as a function of time follows an exponential model of the type T(t) = T₀·edt Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Furthermore, reliable and objective data on the technical efficacy of cooling by this and all other methods is lacking. Very few groups have actually measured whether the desired temperature of 0–4 °C is ever reached in the time that elapses between the beginning of perfusion and actual organ retrieval [41]. In addition, the time span needed to reach adequate cooling via various techniques is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reliable and objective data on the technical efficacy of cooling by this and all other methods is lacking. Very few groups have actually measured whether the desired temperature of 0–4 °C is ever reached in the time that elapses between the beginning of perfusion and actual organ retrieval [41]. In addition, the time span needed to reach adequate cooling via various techniques is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of kidney transplantations as routine terminal treatment of severe kidney failure [6, 7]lead to new aspects in basic renal research: As the donor kidneys are subject to warm and cold ischemia due to the surgical process of explantation, the investigation of the ischemia- and reperfusion-related injuries and consecutive development of reperfusion injury-minimizing techniques could improve graft survival [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…There is surprisingly little literature on kidney temperature during retrieval. In a pig model of multiple organ retrieval, the rate of temperature decrease of the right kidney varied between 0·6°C per min and 1·3°C per min during the procedure, although data from Mikhalski and colleagues suggested that there is some rebound of temperature after the initial cooling by cold flush. They measured kidney temperature during retrieval and observed an average mean(s.d.)…”
Section: Discussionmentioning
confidence: 99%
“…Topical cooling means that the organs are covered with ice slush. Despite these manoeuvres, the kidney cools slowly and its temperature might not reach 0–4°C inside the donor body. Until the kidney has cooled down, best achieved by storage on ice, it will continue to experience higher metabolic rates.…”
Section: Introductionmentioning
confidence: 99%